St. Francis of Asissi: Bioethics in European Middle Ages - Zagorac, Ivana (2011)
St. Francis of Asissi (1181/2–1226) was an extraordinary figure of the Middle Ages. One of the most lovable Christian saints, and contemporary saint patron of ecology, has offered a unique interpretation of interrelation between God, Man, and Nature. The philosophical concept of St. Francis holds no place for hierarchy of beings or a dualism of any kind, not even the one between living and non-living parts of the nature. Egalitarianism of that kind necessary implies acknowledgment of intrinsic value that each and every part of the nature has, as opposite to the well-established way of value attributing in accordance to the standards of human needs. St. Francis of Asissi is widening the term ‘community’ from the community based on the shared religion beliefs, beyond the community of all living creatures, to the community of all creations. The intensity, with which St. Francis has lived his universal love, together with his charismatic figure, made him an archetype of lived sensibility towards the nature. The same implies that he could be declared as the one, maybe even the first one, forerunner of the European bioethics.
Projekt MZOS
ENG